Application of Heutagogical Methods in Entrepreneurship Education - Gál, Tímea; Kovács, Bence; Árváné Ványi, Georgina (International Journal of Engineering and Management Sciences, 2018)
According to Kuit and Fell (2010) the educators’ task is to develop the learners’ lifelong learning skills to be able to apply their skills and competences in and efficient and creative way in new situations in a constantly changing environment. Kamenetz (2010) argues that neither the pedagogical nor the andragogical teaching methods are suitable for performing well in their job, but more and more a self-directed and self-determined approach is needed in which the learner reflects on what and how he learned, and the educator teaches the learner how to teach himself. The concept of heutagogy provides such principles and practices which can give an answer for the above-mentioned challenges in higher education. The authors examined how the heutagogical methods can be adapted at entrepreneurial courses and how the students evaluated these courses.